The Influence of Organizational Culture and Ethics on Public Services at the Medan Satria District Office - Penny Fitri Hapsari; Agus Cholik; Muhammad Rifnaldi; Hardiansyah; Ami Setiasih (Lead Journal of Economy and Administration, 2024)
This study aims to analyze the influence of organizationalculture and ethics on the quality of public services at theMedan Satria District Office. Using a quantitativeapproach and survey method, this study involved 200respondents selected through random samplingtechniques from the community using services in MedanSatria District. Data were collected through a structuredquestionnaire and analyzed using multiple regressionanalysis. The results of the study show that organizationalculture has a positive and significant influence on publicservices with a determination coefficient of 0.642(p<0.05), while ethics contributes positively with a valueof 0.583 (p<0.05). Simultaneously, these two variablesinfluence the quality of public services by 71.5%. Thisfinding indicates the importance of strengtheningorganizational culture and implementing service ethics inimproving the quality of public services at the sub-districtlevel. Research recommendations emphasize thedevelopment of employee training programs andstandardization of ethics-based service procedures.